Identification of Potential and Development of Insta Tourism in Kotagede Yogyakarta - PRAMUSITA, Arina; HANDAYANI, Frida Anis (Journal of Tourism Economics and Policy, 2025)
Instagram is a social media platform that is quite popular, its existence has changed the way people communicate and connect with each other. The popularity and ease of using social media has placed it in various roles, including as a means of promotion. As one of the most popular platform social media,the post of attractive photos and videos on Instagram has increasing the number of tourists visitation inm many destinations. This then gave rise to the term Insta Tourism, which motivates someone to visit instagramable tourist destinations because they want to get interesting content to posting on their social media account. Kotagede is a cultural tourism area that offers the landscape and architecture of the Mataram kingdom that are still authentic and unique. Several tourist spots in Kotagede are one of the tourist destinations for Insta Tourism. This research aims to analyzed the potential of Insta Tourism in Kotagede, so that in the future it can be used as a recommendation for the development and diversification of tourism products. This study uses a qualitative descriptive method by conducting observations and field interviews with tourists, as well as analyzing a number of posts on Instagram about Kotagede tourism.